Giant renal oncocytoma - Stojanović Nebojša; Ignjatović Ivan; Kostov Miloš; Mijović Žaklina; Živković Sladjana; Košević Branko (Vojnosanitetski Pregled)
Background. Renal onkocytoma is a distinctive benign tumor derived from epithelial cells of the distal renal tubules. These tumors are often clinically asymptomatic, diagnosed accidentally and difficult to distinguish from renal cell carcinoma. Case report. We presented a giant renal onkocytoma in a man aged 64, without any signs or symptoms of the urogenital system disorder. The preoperative diagnosis described the tumor mass of the right kidney, size 16 x 14 cm, and indicated a malignant tumor of kidney. The patient underwent radical nephrectomy. The tumor was encapsulated at the intersection with the characteristic central hyaline scar. Microscopically, it was built of uniform polygonal cells with abundant eosinophilic cytoplasm. Immunohystochemiclly, tumor cells were immunoreactive to CK AE1/AE3 and CD 117, but showed negative immunoreactivity to CK 7, RCC marker and Vimentin. Conclusion. Giant renal oncocytomas are rare tumors with benign clinical course. As a rule, they are discovered by accident. Clinical differentiation from malignant tumors of the kidney is not possible. They are treated surgically, mainly by radical nephrectomy. A definitive diagnosis is made only by histopathological examination of tumors using immunohistochemical marker panels.